Upfront & Personal - Nolan, Coleen (London Sidgwick & Jackson, 2009)
Writing with the warmth and humour that have made her so popular, Coleen Nolan describes her eventful life, from joining her sisters' band The Nolans when she was only nine to growing up in the spotlight as they went on to chart-topping success around the world.
Include Illustration
Keywords: Singers -- Television personalities -- Women singers